A relationship between isobaric analog states and shape coexistence in nuclei. (20th April 2018) - Rowe, D J; Wood, J L
Abstract: Two well-known examples of states of very different symmetry in nuclei to those of their neighbours are given by the phenomena of isobaric analog states and nuclear shape coexistence. We show in this letter that they are intimately related.